The role of mechanical engineering in the era of industry 4.0 and society 5.0 - Muji Setiyo; Muhammad Latifur Rochman (Universitas Muhammadiyah Magelang, 2023)
The article delves into the contrasting impacts and roles of Industry 4.0 and Society 5.0 in technological and societal advancement. While Industry 4.0 promises enhanced efficiency and income but raises concerns about automation-driven inequality, mechanical engineering has evolved from traditional to digital realms. Society 5.0, emerging as a response to societal issues, envisions a human-centric society bridging physical and virtual worlds, emphasizing technology for inclusive and sustainable progress. This transformative shift amalgamates human intellect and technology, advocating preparedness and lifelong learning amidst the ongoing industrial revolution. Mechanical engineering's pivotal role spans both paradigms, optimizing Industry 4.0's manufacturing systems and spearheading sustainable solutions and user-centric technologies in Society 5.0, emphasizing a holistic approach to societal and industrial challenges.